PENGARUH KARAKTERISTIK PERSONAL DAN KARAKTERISTIK USAHA TERHADAP TINGKAT PENGEMBALIAN KUPEDES DI PT. BANK RAKYAT INDONESIA ( PERSERO ), Tbk UNIT ADIWERNA II CABANG TEGAL - Ulul Absor (Jurnal Strategik, 2016)
Abstraksi This research takes the title "The Effect of Personal Characteristics and Characteristics of Businesses on Kupedes Return Rate at PT. Bank Rakyat Indonesia (Persero), Tbk Adiwerna II Unit, Tegal Branch ". The aim to be achieved in this study is to find out whether there are any effects of Personal Characteristics and Business Characteristics on Kupedes Return Rate at PT. Bank Rakyat Indonesia (Persero), Tbk Adiwerna II Unit, Tegal Branch. Based on the results of the research that has been done, the author can take several conclusions as follows: The influence of personal characteristics (X1) on the rate of return of Kupedes (Y) is significant. This can be proven in the results of the t-test obtained t-count of 6.318. Compared to the t-table at α = 0.05, it means t-count> t-table or (6.318> 1.66055). And the influence of business characteristics (X2) on the rate of return of Kupedes (Y) is significant. This can be proven in the results of the ttest obtained by t-count of 0.756. When compared to t-table at α = 0.05, it means t-count <t-table or (0.756 <1.66055).